Solving Maine’s Health Care Crisis Requires “Tough Choices” - Wolf, Wendy (Maine Policy Review, 2005)
Wendy Wolf’s commentary discusses the “tough choices” process which invited selected Maine citizens to participate in town hall meeting sessions to provide input on the state’s health plan. She notes that it was easier for participants to agree on health promotion and healthcare delivery processes than for them to make choices about how to pay for healthcare.
Keywords: Maine; healthcare policy